Psychogeography: An (Old) New Method for Viewing the Religious in the Urban and the Sacred - Radford, Raymond (Fieldwork in Religion, 2020)
The way that humanity both inhabits and views its surroundings directly influences individual and collective thoughts and emotions. Yet in a society that is constantly over-stimulated, taking in the surroundings becomes secondary to consumerism, and the distractions inherent within the spectacle. The spectacle, according to Guy Debord and the European revolutionary organization Situationist International (SI), diverted the populace from the reality that surrounds it, and the SI deemed themselves the correct ones to re-envision reality. Fifty years after the 1968 Paris riots, the Situationists no longer exist, but new groups have risen from their ashes to explore and view the world in new ways, groups such as those involved in Urban Exploration (UrbEx). UrbEx involves small, often self-guided groups that investigate the ghosts of modernity, and the detritus of capital that remains in the wake of the spectacle. Utilizing the Situationist International's concept of the dérive, the ideas that fuel urban exploration, and conspiracist ideologies, this article explores the urban world viewed through psychogeography: those who seek the new sacred in a gnostic quest to gain a greater insight into what lurks in the shadows of the myth of modernity.